Biomass-derived graded porous asymmetric coordination monatomic carbon-based electrocatalyst as well as preparation method and application thereof
By stirring and mixing dealkaline lignin with transition metal salt, nitrogen-containing compound and magnesium oxide in a solvent, and pyrolysis is carried out in high temperature after heating and evaporation in a water bath, a biomass-derived graded porous asymmetric coordination single-atom carbon-based electrocatalyst is formed, which solves the problems of low yield and structural defects of the existing Fe-N-C single-atom catalyst synthesis method, and achieves efficient preparation of catalysts with a graded porous structure and an asymmetric Fe-N3O coordination environment, which is suitable for new energy batteries.
Patent Information
- Application Number
- CN202411716260.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-03-11
AI Technical Summary
The existing Fe-N-C single-atom catalyst synthesis methods have problems such as low yield, high toxicity of organic ligands, and complicated synthesis process. Moreover, the lignin-based single-atom catalyst lacks the micropore-mesporous-macroporous graded porous structure and asymmetric Fe-N3O coordination structure, which is difficult to meet the heterogeneous catalytic needs of oxygen reduction reaction.
By stirring and mixing decalin with transition metal salt, nitrogen-containing compound and magnesium oxide in a solvent, a suspension is formed, and after heating and evaporation in a water bath, high-temperature pyrolysis is carried out under the protection of an inert gas to form a biomass-derived staging porous asymmetric coordination single-atom carbon-based electrocatalyst. This method uses coordination chemistry and dual-template agent strategies to construct a micropore-mesoporous-macropore-asymmetric coordination environment.
It realizes the efficient preparation of biomass-derived graded porous asymmetric coordination single-atom carbon-based electrocatalysts, has a microporous-mesoporous-macroporous graded porous structure and a Fe-N3O asymmetric coordination environment, which is suitable for fuel cells and metal air batteries, and improves catalytic activity and yield.
Smart Images

Figure CN119601686A_ABST
Abstract
Description
Technical field:
[0001] The present invention relates to the field of biochar preparation technology and electrocatalytic energy technology, and in particular to a biomass-derived hierarchical porous asymmetric coordinated single-atom carbon-based electrocatalyst and a preparation method and application thereof. Background technology:
[0002] Oxygen reduction reaction (ORR) is an important component of new energy storage and conversion devices such as proton exchange membrane fuel cells and metal-air batteries. However, the slow kinetics of oxygen reduction reaction make the reaction process heavily dependent on the catalytic action of precious metals such as platinum, which restricts the development of these new energy devices. Therefore, it is urgent to develop efficient, economical and environmentally friendly new ORR catalysts to replace the currently used precious metal catalysts. In recent years, single-atom catalysts have attracted extensive attention and research from researchers in various countries due to their high atomic utilization and excellent catalytic activity. In particular, iron-nitrogen-carbon (Fe-NC) single-atom catalysts formed by iron atom anchoring through transition metal-nitrogen-carbon (TM-NC) structures are considered to be promising to replace precious metal catalysts such as platinum carbon in the cathode of fuel cells and metal-air batteries.
[0003] At present, the synthesis method of Fe-NC single-atom catalyst mainly uses imidazole framework molecular sieve material ZIF-8 as template and precursor, and forms nitrogen-doped carbon with rich microporous structure and large specific surface area after carbonization, further adsorbs and anchors Fe ions, and finally introduces Fe-N coordination structure on carbon support by secondary carbonization. This method effectively isolates metal ions and inhibits the aggregation of metal active sites during pyrolysis. However, this method has the disadvantages of low yield, certain toxicity of organic ligands, and cumbersome synthesis process, which is not easy to synthesize on a large scale. At the same time, direct carbonization of ZIF-8 will inevitably lead to the shrinkage of pore structure, resulting in a large number of active sites being buried in the carbon matrix and unable to be fully utilized, reducing the mass specific activity of the catalyst. At the same time, as a multiphase catalytic process, the oxygen reduction process has high requirements for the formation of gas-liquid-solid three-phase boundary. The structural characteristics of ZIF-8, which is mainly micropores and lacks mesopores and macropores, are not conducive to the transmission of oxygen and product transfer at the three-phase boundary of ORR process.
[0004] In view of the difficulty in synthesizing Fe-NC single-atom catalysts and the low yield, researchers tried to use cheaper and more readily available biomass precursors to replace organic ligands to synthesize single-atom catalysts. Lignin, as the third most abundant renewable resource, has a wide range of sources (accounting for 20-30% of the total plant content). It contains three different phenylpropane monomer units and has many oxygen-containing functional groups such as hydroxyl groups, which can anchor metal ions through ion exchange, coordination and other reactions. Therefore, converting biomass waste lignin into single-atom ORR catalysts has huge economic and environmental benefits. At present, some research groups at home and abroad have developed methods to synthesize single-atom catalysts from lignin. For example, Liu Yun's research group at Beijing University of Chemical Technology developed a new method for synthesizing single-atom catalysts through lignin / metal supramolecular independent assembly (ZL201810029041.1). The lignin-based cobalt single atoms developed by their method showed excellent activity in catalyzing the preparation of methyl benzoate from benzyl alcohol; Guo Haiwei and others from Hebei University of Technology developed a new Fe-NC single-atom catalyst using lignin as a carbon source, and successfully applied it in the field of lignin oxidative depolymerization (ZL202310266072.X).
[0005] However, although there have been reports on lignin-based transition metal-nitrogen-carbon single-atom catalysts, the current lignin-based single-atom catalysts still face structural shortcomings similar to ZIF-8, that is, they are mainly microporous and lack mesoporous and macroporous structures, and still cannot meet the needs of heterogeneous catalytic processes such as oxygen reduction reactions involving gases. There are still few reports on how to construct a hierarchical porous structure of micropores-mesopores-macroporous on lignin-based single-atom catalysts. At the same time, the currently reported lignin-derived iron-nitrogen-carbon single-atom catalysts are still mainly based on the Fe-N4 coordination structure. Lignin mainly plays the role of a carbon carrier, and its rich oxygen-containing functional groups have not been fully utilized. How to introduce the O element of lignin into the Fe single-atom coordination environment to form an asymmetric coordination structure still needs in-depth research. Summary of the invention:
[0006] The present invention solves the problems existing in the prior art and provides a biomass-derived hierarchical porous asymmetric coordinated single-atom carbon-based electrocatalyst and a preparation method and application thereof. The biomass-derived hierarchical porous asymmetric coordinated single-atom carbon-based electrocatalyst obtained by the preparation method proposed by the present invention has a micropore-mesopore-macroporous hierarchical porous structure and a surface nanosheet structure, as well as a Fe-N3O coordination structure, and can be applied to fuel cells and metal-air batteries.
[0007] The first object of the present invention is to provide a method for preparing a biomass-derived hierarchical porous asymmetric coordinated single-atom carbon-based electrocatalyst, comprising the following steps: (1) stirring and mixing dealkalized lignin with a transition metal salt, a nitrogen-containing compound, and a template agent magnesium oxide in a solvent to obtain a suspension, wherein the transition metal comprises iron and zinc; (2) heating the suspension obtained in step (1) in a water bath to evaporate and dry to obtain a lignin / metal ion / nitrogen-containing compound / template agent mixed precursor; (3) pyrolyzing the mixed precursor obtained in step (2) at a high temperature under the protection of an inert gas, cooling, washing, and drying in sequence to obtain the biomass-derived hierarchical porous asymmetric coordinated single-atom carbon-based electrocatalyst.
[0008] The present invention utilizes coordination chemistry combined with a dual template strategy, uses lignin as an organic ligand and carbon source, utilizes the rich oxygen-containing functional groups on the surface of lignin to anchor metal ions, and utilizes the high-temperature volatility of zinc ions and the high-temperature stability of MgO to form a soft and hard dual template to construct a hierarchical porous structure. The introduction of metal zinc ions during the carbonization process is beneficial to increasing the number of micropores in the carbon material, because as the temperature of the carbonization process increases, zinc ions are gradually converted into ZnO and then reduced to metal Zn by a carbon thermal reaction (ZnO+C→Zn+CO2). When the temperature rises to 900°C, metal Zn volatilizes to cause more defects and microporous structures to appear on the surface of the carbon material. The magnesium oxide template undergoes a hydrogen oxidation reaction on the surface during the evaporation of the solvent, generating Mg(OH)2 that combines with lignin and covers the surface of lignin to induce the formation of a carbon nanosheet structure. The carbonization process is beneficial to inhibiting the aggregation of surface metal ions. During the high-temperature carbonization process, nitrogen-containing compounds gradually decompose to produce ammonia that is doped onto the carbon, forming anchoring sites such as pyridinic nitrogen and pyrrolic nitrogen, which can coordinate with Fe ions to form highly active Fe-N3O sites.
[0009] Preferably, the solvent in step (1) is deionized water, and the mass volume ratio of lignin to deionized water is 1:100-1:150 g / mL.
[0010] Preferably, in step (1), the iron salt is one or more of ferric nitrate nonahydrate, ferric chloride and ferrous oxalate, and the zinc salt is one or more of zinc nitrate hexahydrate, zinc acetate dihydrate and zinc chloride.
[0011] Preferably, in step (1), the mass ratio of dealkalized lignin to iron salt is 5:1-20:1, and the molar ratio of iron salt to zinc salt is 1:10-1:30.
[0012] More preferably, in step (1), the mass ratio of dealkalized lignin to iron salt is 10:1, and the molar ratio of iron salt to zinc salt is 1:20.
[0013] Preferably, the nitrogen-containing compound in step (1) is selected from one or more of dicyandiamide, urea and melamine, the mass ratio of the nitrogen-containing compound to the dealkalized lignin is 1:2-2:1, and the mass ratio of the magnesium oxide to the dealkalized lignin is 1:3-2:1.
[0014] Further preferably, the mass ratio of the nitrogen-containing compound to the dealkalized lignin in step (1) is 1:1, and the mass ratio of the magnesium oxide template to the dealkalized lignin is 1:1.3.
[0015] The specific steps of step (2) are: heating and stirring the above suspension in a 75°C water bath until the solvent evaporates, and further placing it in a 60°C vacuum drying oven for drying to obtain a lignin / metal ion / nitrogen-containing compound / template mixed precursor.
[0016] The inert gas described in step (3) is nitrogen or argon; the template agent magnesium oxide is a flaky structure.
[0017] Preferably, the high temperature pyrolysis conditions in step (3) are: pyrolysis temperature is 900°C-1000°C, holding time is 0.5-3h, and heating rate is 3-20°C / min.
[0018] Further preferably, the high temperature pyrolysis conditions in step (3) are: pyrolysis temperature is 910°C, holding time is 1h, and heating rate is 5°C / min.
[0019] Preferably, the specific steps of washing and drying (acid washing, water washing and drying) are: dispersing the product in a 1M hydrochloric acid solution and stirring overnight, filtering to remove the hydrochloric acid and washing with deionized water to pH = 6-7, then placing it in a 60°C vacuum drying oven, drying and then grinding to obtain a biomass-derived hierarchical porous asymmetric coordinated single-atom carbon-based electrocatalyst.
[0020] The second object of the present invention is to provide a biomass-derived hierarchical porous asymmetric coordinated single-atom carbon-based electrocatalyst obtained by the above-mentioned preparation method, wherein the single-atom carbon-based electrocatalyst simultaneously has a hierarchical porous structure of micropores-mesopores-macropores, a surface nanosheet structure and an asymmetric Fe-N3O coordination environment.
[0021] The third object of the present invention is to provide the biomass-derived hierarchical porous asymmetric coordinated single-atom carbon-based electrocatalyst that can be applied to microbial fuel cells or metal-air battery cathodes.
[0022] Preferably, the single-atom carbon-based electrocatalyst is used as the cathode of a zinc-air battery or a cathode of a microbial fuel cell.
[0023] Compared with the prior art, the present invention has the following advantages:
[0024] 1. Lignin contains a large number of oxygen-containing functional groups that can anchor metal ions, and is inexpensive as an organic ligand and carbon source;
[0025] 2. The present invention realizes the preparation of hierarchical porous carbon-based single atoms through a simple process, which is easy to scale up production.
[0026] 3. The biomass-derived hierarchical porous asymmetric coordinated single-atom carbon-based electrocatalyst obtained by the preparation method proposed in the present invention has a hierarchical porous structure of micropores-mesopores-macropores.
[0027] 4. The biomass-derived hierarchical porous single-atom carbon-based electrocatalyst obtained by the preparation method proposed in the present invention has an Fe-N3O asymmetric coordination structure. Description of the drawings:
[0028] Figure 1 This is a scanning electron microscope image of the biomass-derived hierarchical porous asymmetric coordinated single-atom carbon-based electrocatalyst obtained in Example 1;
[0029] Figure 2 This is a transmission electron microscopy image of the biomass-derived hierarchical porous asymmetric coordinated single-atom carbon-based electrocatalyst obtained in Example 1;
[0030] Figure 3 This is a spherical aberration corrected transmission electron microscopy image of the biomass-derived hierarchical porous asymmetric coordinated single-atom carbon-based electrocatalyst obtained in Example 1;
[0031] Figure 4 The X-ray extended edge fitting coordination structure of the biomass-derived hierarchical porous asymmetric coordinated single-atom carbon-based electrocatalyst obtained in Example 1;
[0032] Figure 5 This is a scanning electron microscope image of the biomass-derived microporous single-atom carbon-based electrocatalyst obtained in Example 2;
[0033] Figure 6 This is a transmission electron microscopy image of the biomass-derived microporous single-atom carbon-based electrocatalyst obtained in Example 2;
[0034] Figure 7 This is a scanning electron microscope image of the biomass-derived mesoporous single-atom carbon-based electrocatalyst obtained in Example 3;
[0035] Figure 8 The nitrogen adsorption-desorption curves of the single-atom carbon-based electrocatalysts obtained in Example 1, Example 2, and Example 3;
[0036] Fig. 9 DFT pore size distribution analysis corresponding to the nitrogen adsorption / desorption curves of the single-atom carbon-based electrocatalysts obtained in Example 1, Example 2, and Example 3;
[0037] Fig.10This is a comparison curve of the ORR catalytic performance LSV test of the biomass-derived hierarchical porous asymmetric coordinated single-atom carbon-based electrocatalyst and the commercial platinum-carbon catalyst under alkaline conditions in Example 4;
[0038] Fig.11 This is a comparison curve of the ORR catalytic performance LSV test of the biomass-derived hierarchical porous asymmetric coordinated single-atom carbon-based electrocatalyst and the commercial platinum-carbon catalyst under neutral conditions in Example 5;
[0039] Fig.12 This is the charge and discharge test curve of the zinc-air battery assembled in Example 6;
[0040] Fig.13 Figure 6 shows a zinc-air battery-driven electronic device assembled for Example 6;
[0041] Fig.14 This is the LSV test comparison curve of ORR catalytic performance of samples with different pyrolysis temperatures under alkaline conditions in Example 7;
[0042] Fig.15 This is a comparison curve of the LSV test of the ORR catalytic performance of different zinc acetate dihydrate samples under alkaline conditions in Example 8. Specific implementation method:
[0043] The following examples are provided to further illustrate the present invention, rather than to limit the present invention.
[0044] Unless otherwise defined, all professional terms used hereinafter have the same meaning as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specified, the experimental materials and reagents herein are conventional commercial products in the art. Dealkalized lignin was purchased from Shanghai McLean Biochemical Technology Co., Ltd., item number: L849279.
[0045] Example 1
[0046] The synthesis of biomass-derived hierarchical porous asymmetric coordinated single-atom carbon-based electrocatalysts comprises the following steps:
[0047] 1) Take a 100mL beaker and add 60mL deionized water, add 0.438g zinc acetate dihydrate (2mmol) and stir until dissolved, use a pipette to take 200μL 200mg / mL Fe(NO3)3 solution (10mg Fe(NO3)3·9H2O dissolved in deionized water, add 5.726mL 36%-38% concentrated hydrochloric acid to acidify, and dilute to 50mL), stir until the solution color is uniform. Take 0.4g lignin and 0.3g MgO and add them to the above solution, stir until the lignin is completely dispersed, then add 0.4g melamine;
[0048] 2) placing the beaker in a water bath and stirring at 75° C. until the solution is completely evaporated, and then placing the evaporated solid in a vacuum drying oven at 60° C. overnight to further dry the precursor in a powder form;
[0049] 3) placing the powdered precursor in a porcelain boat, pyrolyzing it at 910°C in a vacuum tube furnace under a nitrogen atmosphere at a heating rate of 5°C / min, and cooling it naturally to room temperature after maintaining the temperature for 1 hour to obtain powdered carbon;
[0050] 4) Grind the powdered carbon, disperse it in 50 mL of 1 M hydrochloric acid solution, stir overnight, filter and wash with deionized water until pH = 6-7, dry it in a vacuum oven at 60°C, and grind it evenly to obtain a biomass-derived hierarchical porous single-atom carbon-based electrocatalyst.
[0051] The obtained biomass-derived hierarchical porous asymmetric coordinated single-atom carbon-based electrocatalyst was tested, and its scanning electron microscope photo is shown in the figure. Figure 1 As shown in the transmission electron microscopy photograph Figure 2 As shown in Figure 2, a large number of porous nanosheet structures are generated on the surface of the material. Figure 3 As shown, the bright spots in the photo are the single-atom sites of Fe. Figure 4 This is the coordination structure obtained by X-ray extended edge fitting. The coordination structure of Fe single atom is Fe-N3O. Figure 8 and Fig. 9 It shows that the pore structure of biomass-derived hierarchical porous asymmetric coordinated single-atom carbon-based electrocatalysts contains a large number of micropores as well as mesopores and macropores.
[0052] Embodiment 2:
[0053] The same as Example 1, except that: the biomass-derived microporous single-atom carbon-based electrocatalyst is not added with MgO template agent during the raw material mixing stage to obtain the biomass-derived microporous single-atom carbon-based electrocatalyst.
[0054] The scanning electron microscope photos are as follows Figure 5 As shown in the transmission electron microscopy photograph Figure 6 As shown, the material is a block structure. Figure 8 and Fig. 9 It shows that the pore structure of biomass-derived microporous single-atom carbon-based electrocatalysts is mainly micropores.
[0055] Embodiment 3:
[0056] The method is the same as Example 1, except that zinc acetate dihydrate is not added to the biomass-derived mesoporous single-atom carbon-based electrocatalyst during the raw material mixing stage to obtain the biomass-derived mesoporous single-atom carbon-based electrocatalyst.
[0057] The scanning electron microscope photos are as follows Figure 7As shown, nanosheet structures appeared on the surface. Figure 8 and Fig. 9 It shows that the biomass-derived mesoporous single-atom carbon-based electrocatalyst forms an obvious mesoporous structure.
[0058] Example 4: Evaluation of oxygen reduction activity of electrocatalysts under alkaline conditions
[0059] 5 mg of catalyst (biomass-derived hierarchical porous asymmetric coordinated single-atom carbon-based electrocatalyst obtained in Example 1 / / commercial platinum carbon) was dispersed in 1 mL of ethanol / water solution (the volume ratio of ethanol to water was 1:1), and then 10 μL of 5% Nafion solution was added, and ultrasonicated for 1 h to obtain a uniformly dispersed catalyst ink. 10 μL of catalyst ink was added to the platinum carbon electrode with a pipette, and assembled on a rotating disk electrode device after drying at room temperature, with a graphite rod as the counter electrode, mercury / mercuric oxide as the reference electrode, and 0.1 M KOH as the electrolyte to form a three-electrode system. Under the conditions of a scan rate of 10 mV / s and a rotation speed of 1600 rpm, the catalyst was subjected to linear sweep voltammetry measurement in the voltage range of -0.6 to 0.3 V relative to the reference electrode to obtain the ORR performance of the catalyst. Fig.10 It shows that the half-wave potential of the ORR process of biomass-derived hierarchical porous asymmetric coordinated single-atom electrocatalyst under alkaline conditions is higher than that of commercial platinum-carbon catalysts.
[0060] Example 5: Evaluation of oxygen reduction activity of electrocatalysts under neutral conditions
[0061] The same as Example 4, except that: 50 mM PBS solution is used as the electrolyte and saturated silver / silver chloride is used as the reference electrode to form a three-electrode system. Fig.11 It shows that the half-wave potential of the ORR process of biomass-derived hierarchical porous asymmetric coordinated single-atom carbon-based electrocatalysts under neutral conditions is higher than that of commercial platinum-carbon catalysts.
[0062] Example 6: Application of biomass-derived hierarchical porous asymmetric coordinated single-atom carbon-based electrocatalysts in rechargeable zinc-air batteries
[0063] The biomass-derived hierarchical porous asymmetric coordinated single-atom carbon-based electrocatalyst synthesized in Example 1 and the commercial oxidant were mixed in a mass ratio of 1:1, and the catalyst ink was prepared according to the method in Example 3, and the ink was dripped on the hydrophobic carbon cloth and dried as the air cathode (the area of the catalyst loaded on the carbon cloth was 1 cm -2 , the catalyst loading was 3 mg cm -2 ). The air cathode and the polished zinc sheet were assembled on a zinc-air battery mold and 6 mol L -1 The KOH solution was used as the electrolyte of the zinc-air battery. The battery test system was used to carry out charge and discharge tests on the assembled zinc-air battery. Fig.12 The zinc-air battery assembled with biomass-derived hierarchical porous asymmetric coordinated single-atom carbon-based electrocatalysts can operate stably for 200 h. Fig.13 The assembled zinc-air battery can drive an electronic device timer.
[0064] Embodiment 7:
[0065] The same as Example 1, except that the pyrolysis temperature is set to 850°C.
[0066] Its electrochemical properties such as Fig.14 As shown in the figure, the performance of the 850℃ sample under alkaline conditions is lower than that of the 910℃ sample. The reason is that the zinc ions cannot be completely volatilized at 850℃ and the degree of graphitization of the sample is low.
[0067] Embodiment 8:
[0068] Same as Example 1, except that:
[0069] Two groups of samples with different addition amounts of zinc acetate dihydrate were added, 0.329 g (1.5 mmol) and 0.548 g (2.5 mmol), respectively, to form a control experiment with Example 1. The ORR performance of different addition amounts of zinc acetate dihydrate is shown in FIG. Fig.15 As shown, it can be seen that zinc acetate in Example 1 is the optimal addition amount.
[0070] Embodiment 9:
[0071] Same as Example 1, except that:
[0072] The mass ratio of dealkalized lignin to iron salt is 5:1, and the molar ratio of iron salt to zinc salt is 1:10; the mass ratio of nitrogen-containing compound to dealkalized lignin is 1:2, and the mass ratio of magnesium oxide to dealkalized lignin is 1:3; the high-temperature pyrolysis conditions are: pyrolysis temperature is 900°C, holding time is 3h, and heating rate is 3°C / min.
[0073] Embodiment 10:
[0074] Same as Example 1, except that:
[0075] The mass ratio of dealkalized lignin to iron salt is 20:1, and the molar ratio of iron salt to zinc salt is 1:30; the mass ratio of nitrogen-containing compound to dealkalized lignin is 2:1, and the mass ratio of magnesium oxide to dealkalized lignin is 2:1; the high-temperature pyrolysis conditions are: pyrolysis temperature is 1000°C, insulation time is 0.5h, and heating rate is 20°C / min.
[0076] The description of the above embodiments is only used to help understand the technical solution and core ideas of the present invention. It should be pointed out that for technicians in this technical field, several improvements and modifications can be made to the present invention without departing from the principles of the present invention. These improvements and modifications also fall within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a biomass-derived hierarchical porous asymmetric coordinated single-atom carbon-based electrocatalyst, characterized in that: The method comprises the following steps: (1) mixing dealkalized lignin with a transition metal salt, a nitrogen-containing compound and a template agent magnesium oxide in a solvent and stirring the mixture to obtain a suspension, wherein the transition metal comprises iron and zinc; (2) heating and evaporating the suspension obtained in step (1) and drying the mixture to obtain a lignin / metal ion / nitrogen-containing compound / template agent mixed precursor; and (3) subjecting the mixed precursor obtained in step (2) to high-temperature pyrolysis under the protection of an inert gas, and washing and drying the mixture after cooling to obtain a biomass-derived hierarchical porous asymmetric coordinated single-atom carbon-based electrocatalyst.
2. The preparation method according to claim 1, characterized in that: In step (1), the iron salt is one or more of ferric nitrate nonahydrate, ferric chloride and ferrous oxalate, and the zinc salt is one or more of zinc nitrate hexahydrate, zinc acetate dihydrate and zinc chloride.
3. The preparation method according to claim 1, characterized in that: The solvent described in step (1) is deionized water, and the mass volume ratio of lignin to deionized water is 1:100-1:150 g / mL.
4. The preparation method according to any one of claims 1 to 3, characterized in that In step (1), the mass ratio of dealkalized lignin to iron salt is 5:1-20:1, and the molar ratio of iron salt to zinc salt is 1:10-1:
30.
5. The preparation method according to claim 1, characterized in that: The nitrogen-containing compound in step (1) is selected from one or more of dicyandiamide, urea and melamine, the mass ratio of the nitrogen-containing compound to the dealkalized lignin is 1:2-2:1, and the mass ratio of the magnesium oxide to the dealkalized lignin is 1:3-2:
1.
6. The preparation method according to claim 1, characterized in that: The high temperature pyrolysis conditions described in step (3) are: pyrolysis temperature is 900°C-1000°C, insulation time is 0.5-3h, and heating rate is 3-20°C / min.
7. The preparation method according to claim 1, characterized in that: The template magnesium oxide described in step (1) is a flake structure.
8. The biomass-derived hierarchical porous asymmetric coordinated single-atom carbon-based electrocatalyst obtained by the preparation method of claim 1, characterized in that: The single-atom carbon-based electrocatalyst has an asymmetric coordination structure of Fe-N3O, and also has a hierarchical porous structure of micropores-mesopores-macropores and a surface nanosheet structure.
9. The biomass-derived hierarchical porous asymmetric coordinated single-atom carbon-based electrocatalyst described in claim 8 can be applied to microbial fuel cells or metal-air battery cathodes.
Citation Information
Patent Citations
Preparation method of efficient and stable porous M-N-C catalyst
CN113809340A
Preparation method and application of lignin-metal compound derived catalyst
CN114308095A
Preparation method and application of lignin-derived carbon-anchored monatomic catalyst
CN115970732A
Efficient ORR electrocatalyst and preparation method thereof
CN117199405A
Cited By
Platinum monatomic-platinum nanoparticle synergistic dispersion catalyst as well as preparation method and application thereof
CN120914271A